TITLE: COMPARATIVE ANALYSIS OF INTERCULTURAL COMMUNICATION: GESTURES IN SLOVAK, AMERICAN, AND UZBEK CULTURES - Uktamova Ozodakhon Ilhomjon kizi (TADQIQOTLAR.UZ, 2024)
This thesis examines the role of gestures in intercultural communication across Slovak, American, and Uzbek cultures. Focusing on both common and culturally unique gestures, the study identifies how gestures reflect each culture’s underlying values and communication norms. Using interviews and observational data, the findings reveal that while American gestures are often open and expressive, Slovak gestures tend to be more restrained, and Uzbek gestures emphasize respect and hierarchy. These differences have implications for effective cross-cultural communication and understanding in increasingly globalized interactions.